Las técnicas activas en el desarrollo del pensamiento lógico-matemático en los niños de quinto año de Educación General Básica de la Unidad Educativa “Federico González Suárez” de la parroquia Matriz cantón Alausí provincia de Chimborazo, durante el año 2014-2015 - Lunavictoria Padilla, Jenny Alexandra (2016)
The research work was developed in the Educational Unit “Federico Gonzalez Suarez” of the matrix parish, Alausi canton, province of Chimborazo, during the 2014-2015 school year, taking as a group of study to the children of the fifth year of General Basic Education. The research used the inductive – deductive method; its design was quasi – experimental; the type was documentary and of field, its level was diagnostic and exploratory. The population was composed of 35 children in fifth year and 2 teachers of mathematics. With the preliminary observation of the development of activities in the area of mathematics were the shortcomings of the students were detected in the development of numerical thinking, space, metric and random thinking, as well as in the management of the money. It was chosen the technique of the game for the reinforcement of the learning. The application of the active technique allowed substantially to improve the skills of student to develop exercises and problems in the five topics covered in the mathematical logical thinking, making the removal of the option is not observed in all aspects. It is concluded that the active techniques are valuable tools of learning that contribute to the development of the skills of students because they promote the integration of the group, the permanent interaction and increased performance.